Performance of students in project-based science classrooms on a national measure of science achievement - Schneider, Rebecca M.; Krajcik, Joseph S.; Marx, Ronald W.; Soloway, Elliot (Journal of Research in Science Teaching, 2002)
Reform efforts in science education emphasize the importance of supporting students' construction of knowledge through inquiry. Project-based science (PBS) is an ambitious approach to science instruction that addresses concerns of reformers. A sample of 142 10th- and 11th-grade students enrolled in a PBS program completed the 12th-grade 1996 National Assessment of Educational Progress (NAEP) science test. Compared with subgroups identified by NAEP that most closely matched our student sample, White and middle class, PBS students outscored the national sample on 44% of NAEP test items. This study shows that students participating in a PBS curriculum were prepared for this type of testing. Educators should be encouraged to use inquiry-based approaches such as PBS to implement reform in their schools. © 2002 Wiley Periodicals, Inc. J Res Sci Teach 39: 410–422, 2002
Keywords: apprentissage par projet